Effects of SA237, a humanized anti‐interleukin‐6 receptor monoclonal antibody, on pre‐ and postnatal development in cynomolgus monkey. Issue 11 (15th May 2017) - Katagiri, Ryuichi; Ishihara‐Hattori, Kana; Frings, Werner; Amano, Jun; Fuchs, Antje; Chiba, Shuichi
Abstract : Background: SA237 is a humanized anti‐interleukin‐6 receptor (IL‐6R) monoclonal antibody in which the constant and variable regions have been engineered for a longer plasma half‐life. According to literature, blocking of IL‐6 related functions could have an influence on pregnancy sustainment, development of the immune system, and brain growth. Methods: SA237 effects on dams, embryo‐fetal development, parturition and postnatal development were investigated in an enhanced pre‐ and postnatal development study, in which SA237 was subcutaneously administered to pregnant cynomolgus monkeys at dose levels of 2 or 50 mg/kg once weekly from gestation day 20 until parturition. Infant development, including immune function and learning ability tests, was comprehensively assessed at multiple examinations until approximately 10 months after birth. Results: SA237 plasma concentrations were almost equivalent between dams and their infants and dropped throughout the postnatal period, pharmacologically relevant exposure was maintained for 147 days after birth at 50 mg/kg. Because the binding of SA237 to IL‐6R inhibited IL‐6R‐mediated clearance of IL‐6, serum IL‐6 increased in dams and infants. However, there were no SA237‐related adverse effects on dams, embryos, fetuses, or infants. SA237 pharmacological effects contributed to the suppression of plasma cell differentiation and antibody production by inhibiting IL‐6 signaling, and T cell‐dependent antibody reaction was minimally suppressed in infants, but physiological immunoglobulin class switching and general antibody production against a T cell‐dependent antigen were maintained. Conclusion: The exposure to SA237 did not adversely affect dams, embryo‐fetal development, parturition, and postnatal development, including immune function and neuronal development. Birth Defects Research 109:843–856, 2017. © 2017 Wiley Periodicals, Inc.